Work Shown:
f(x) = 3x + 2
f(-2) = 3(-2) + 2 ... each x replaced with -2
f(-2) = -6 + 2
f(-2) = -4
g = w + 2
w = g + 8
w = g − 2
w = 8g
w = g + 2
g = w + 8
g = w − 2
The standard equation of a circle is expressed as:
Given a circle whose equation is
Get the centre of the circle
2gx = -2x
2g = -2
g = -1
Similarly, 2fy = 0
f = 0
Centre = (-(-1), 0) = (1, 0)
This shows that the center of the circle lies on the x-axis
r = radius = √g²+f²-C
radius = √1²+0²-(-8)
radius =√9 = 3 units
The radius of the circle is 3 units.
For the circle x² + y² = 9, the radius is expressed as:
r² = 9
r = 3 units
Hence the radius of this circle is the same as the radius of the circle whose equation is x² + y² = 9.
Learn more on circles here: brainly.com/question/23226948
Answer:
a, b and e
Step-by-step explanation:
i got it correct on edge
B. length − width − height
C. length + width + height
D. length × width × height
Answer:
D. length × width × height
Step-by-step explanation:
That is how you calculate the volume of a shape.